The Concise Dictionary of Classical Hebrew - Clines, David J.A. (Sheffield, UK : Sheffield Phoenix Press, 2009)
This is an abridgment of the 8-volume Dictionary of Classical Hebrew ... Like it (and unlike all previous Hebrew dictionaries) all the literature of classical Hebrew is covered, including not only the Hebrew Bible but also the Dead Sea Scrolls, Ben Sira and the ancient Hebrew inscriptions. The CDCH thus contains not only the c. 8400 Hebrew words found in the standard dictionaries, but also a further 3340+ words (540 from the Dead Sea Scrolls, 680 from other ancient Hebrew literature, and 2120+ proposed words for the Hebrew Bible not previously recognized by dictionaries). The CDCH has been designed to be as user-friendly as possible. All the Hebrew quoted is accompanied by an English translation. At the end of each entry on verbs is a list of the nouns derived from that verb; and at the end of each entry on nouns a reference to the verb from which it is derived (when known). Rich in examples and citations, and preserving the important statistical information contained in the DCH, this edition will be of immense value to students at all levels, as well as to working scholars who will not always be in a position to refer to the complete DCH.
An abridgment of the 8-volume Dictionary of Classical Hebrew.
Keywords: Bible -- language, style; Hebrew language -- dictionaries -- English